Extractions of Aspergillus flavus link ex grray and cladosporium Cladosporioides (Fresen.) de vries from allergenic microfungi and application of toxicity tests - (:unkn) unknown (My University, 2002)
Aspergillus flavus Link ex Gray ve Cladosporium cladosporioides (Fresen.) de Vries Türkiye'de ilk defa Florya Atatürk Ormanı toprağından izole edilmiş, ekstreleri hazırlanmış ve toksik etkilerini tayin etmek için fareler üzerinde toksisite testi uygulamaları yapılmıştır. Ekstraksiyonlar literatürdeki metoda uygun olarak hazırlanmıştır. Bu maksatla ekstraktif olarak Coca solüsyonu, sterilizasyon için steril filtrasyon tekniği kullanılmıştır. Stok çözeltiler toksisite testi uygulamalarından önce 1/10 oranında seyreltilmiştir. Hazırlanan A. flavus Link ex Gray ve C. cladosporioides (Fresen.) de Vries ekstrelerinin steril olduğu ve 10 fare üzerindeki deneyde toksik olmadığı bulunmuştur.

Aspergillus flavus Link ex Gray and Cladosporium cladosporioides (Fresen.) de Vries, isolated from the soil of Florya Atatürk Forest, were extracted and some toxicity tests were carried out in order to determine their toxic effects on mice for the first time in Turkey. The method of extraction complied with the one described in the literature. During the process, Coca's solution was used as an extractive agent. Sterile filtration was employed in the sterilization process. The stocks were diluted to 1/10 of their concentrations before the toxicity tests were carried out. It was found that the A. flavus Link ex Gray and C. cladosporioides (Fresen.) de Vries extracts were sterile and that the experiments performed on 10 mice proved to be not toxic.
Allerjenik mikrofunguslardan aspergillus flavus link ex gray ve cladosporium cladosporioides (Fresen.) de vries' in ekstrelerinin hazırlanması ve toksisite testi uygulamaları
Keywords: Biyoloji